La gestión financiera en la toma de decisiones de la cooperativa sagrada familia ltda. de la ciudad de Riobamba, en los períodos 2014 – 2015. - Aucanshala Naula, Jorge Gonzalo (2017)
This research project was developed with the objective of establishing a relationship between the financial management and the decision making of the entity. After elaborating the problem which was based on the current situation of the cooperative, the reason, relevance of the research and objectives were stated and justified. The theoretical framework consisted of three units. The first unit was constituted by general information of the Sagrada Familia Ltda such as: historical review, philosophy, organizational objectives, services and structure. Units two and three presented theoretical aspects related to financial management and decision making, respectively. The methodological framework describes the deductive method used from general knowledge, the type of research was documentary and field, its design was non – experimental and is level was descriptive. The population was composed by the board, employees and partners. The first two were interviewed and partners were surveyed. In addition, the financial information for the periods 2014 – 2015 was taken into account. All this information collected was subjected to analysis and interpretation. From discussion and analysis of opinions expressed by the study population and from observation an analysis of the financial statements, the conclusions of the research were obtained, which correspond to the specific objectives. For each conclusion, a recommendation was made to improve the soundness of the financial management of Sagrada Familia Ltda. Cooperative.